The Influence of Trait Emotion and Spatial Distance on Risky Choice Under the Framework of Gain and Loss - Xu, Fuming; Huang, Long (Frontiers in Psychology, 2022)
Human’s decision-making on the same event will be affected by different descriptions of the event’s gain or loss framework; this phenomenon is known as the framework effect. With the continuous expansion and in-depth study of frame effects in the field of risk decision-making, researchers have found that the are quite different in different situations. People have different interpretations of the same event at different psychological distances, and will also be affected by their own emotions. Therefore, this study examines the common influence of task frame, spatial distance, and trait emotion on risk selection through two studies. Study 1 uses a 2 (framework: gain vs. loss) × 2 (trait sentiment: high vs. low) inter-subject design, and the dependent variable is the choice of the rescue plan for the classic “Asian disease” problem. The results revealed that the main effect of framing and trait anxiety was significant, that of trait anger was not significant, and there was no significant interaction effect between trait emotion and framing effect. Study 2 uses a 2 (spatial distance: far vs. near) × 2 (decision framework: gain vs. loss) × 2 (trait sentiment: high vs. low) three-factor inter-subject design in which the dependent variable is the choice of rescue plan. The results indicate that the main effects of spatial distance and trait anxiety are significant, those of framing and trait anger are not significant, and the framing effect and spatial distance have significant interaction effects. Furthermore, there is no significant interaction effect between trait emotion, spatial distance, and framing effects. In general, trait emotion has a weak predictive effect on risk decision-making. Spatial distance has a strong predictive effect on risk selection and significantly regulates the framing effect in risk decision-making.